Answer:
is the equivalent expression as
is equal to
.
Step-by-step explanation:
Considering the expression
![2s+\left(-4s\right)](https://tex.z-dn.net/?f=2s%2B%5Cleft%28-4s%5Cright%29)
As we know that
- Like terms are said to be the terms which hold the same variables raised to the same power.
- For example,
and
are like terms as they contain the same variable
raised to the same power.
Lets solve the expression
![2s+\left(-4s\right)](https://tex.z-dn.net/?f=2s%2B%5Cleft%28-4s%5Cright%29)
![\mathrm{Remove\:parentheses}:\quad \left(-a\right)=-a](https://tex.z-dn.net/?f=%5Cmathrm%7BRemove%5C%3Aparentheses%7D%3A%5Cquad%20%5Cleft%28-a%5Cright%29%3D-a)
![2s-4s](https://tex.z-dn.net/?f=2s-4s)
![\mathrm{Add\:similar\:terms:}\:2s-4s=-2s](https://tex.z-dn.net/?f=%5Cmathrm%7BAdd%5C%3Asimilar%5C%3Aterms%3A%7D%5C%3A2s-4s%3D-2s)
![-2s](https://tex.z-dn.net/?f=-2s)
Therefore,
is the equivalent expression as
is equal to
.
Keywords: equivalent expression, like terms
Learn more about equivalent expression from brainly.com/question/8902137
#learnwithBrainly
Answer:
8.944271909999
Step-by-step explanation:
hope you happy
Answer:
180
Step-by-step explanation:
Hello!
This question is about which values you are changing when you are transforming an equation.
Let's go through the parent function for an absolute value equation and its various transformations.
![y=a|b(x-c)|+d](https://tex.z-dn.net/?f=y%3Da%7Cb%28x-c%29%7C%2Bd)
Since we are only looking at horizontal and vertical transformations, we only need to worry about the c and d values.
The c value of a function determines a function's horizontal position, and the d value of a function determines a function's vertical position.
One thing to note here is that the c value is being subtracted from the x value, meaning that if the function is being transformed to the right, you would actually be subtracting that value, while the d value behaves like a normal value, if it is being added, the function is transformed up, and vice versa.
Now that we know this, let's write each expression.
a) ![y=|x+2|+1](https://tex.z-dn.net/?f=y%3D%7Cx%2B2%7C%2B1)
b) ![y=|x+2|-1](https://tex.z-dn.net/?f=y%3D%7Cx%2B2%7C-1)
c) ![y=|x+3|](https://tex.z-dn.net/?f=y%3D%7Cx%2B3%7C)
d) ![y=|x+1|](https://tex.z-dn.net/?f=y%3D%7Cx%2B1%7C)
Hope this helps!